2020
DOI: 10.1016/j.invent.2020.100336
|View full text |Cite
|
Sign up to set email alerts
|

Using a blended format (videoconference and face to face) to deliver a group psychosocial intervention to parents of autistic children

Abstract: Background Parents and carers of autistic children report poor mental health. Autism stigma is a strong contributing factor to poor parental mental health, yet there are currently no interventions available that are evidenced to improve parents' mental health in part through increasing resilience to stigma. Childcare and travel are well known barriers to attendance and attrition rates for this population are high. Methods A blended format psychosocial group support inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Technology such as a smartphone applications can be harnessed to provide this. Establishing dedicated emotional support provisions, for example, through formal parent support networks or a group psychosocial intervention (Lodder et al, 2020) will also be useful for parents. This could potentially offer the ASD community with a platform to gather and support each other.…”
Section: Rele Van Ce To Clini C Al Pr Ac Ti Cementioning
confidence: 99%
“…Technology such as a smartphone applications can be harnessed to provide this. Establishing dedicated emotional support provisions, for example, through formal parent support networks or a group psychosocial intervention (Lodder et al, 2020) will also be useful for parents. This could potentially offer the ASD community with a platform to gather and support each other.…”
Section: Rele Van Ce To Clini C Al Pr Ac Ti Cementioning
confidence: 99%
“…Group-based therapy provided psychosocial support for parents of a child with ASD ( Farmer and Reupert, 2013 ), and videoconferencing was an acceptable and feasible approach of delivery for group-based interventions in this population ( Parsons et al, 2017 ; Lodder et al, 2020 ). In a recent systematic review ( Sutherland et al, 2018 ), parent satisfaction was reported as an outcome variable in nine of fourteen studies, and only three studies were intervention design via telehealth, with all three reporting a high level of satisfaction ( Ingersoll and Berger, 2015 ; Hepburn et al, 2016 ; Pickard et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…for practice and repetition of training as needed; 4) written guides for different technology platforms that give step-by-step instructions, including for how to set up IDs and passwords, sent out with appointment letters; 5) brief and direct training sessions offered to service users before their online appointment, doing a trial run of using the technology beforehand, or increasing virtual contact duration to accommodate learning. CMO 1.4: Impact of technology related disruptions [38,55,66,[86][87][88][89][90][91][92] When technological issues (including connection problems and device issues) lead to disruptions to online sessions and there is no pre-arranged backup method of contact (e.g. a plan to connect by telephone instead of video-call if needed) (C), the quality of the intervention is diminished (O1) there is a loss of empathic connection between client and therapist (O2) and the sessions may not be able to continue (O3), as the flow of the conversation is interrupted and session time reduced, for example, when having to ask the other person to repeat what has been said, or when cut off completely, leaving staff and service users potentially feeling distracted, frustrated, awkward and upset (particularly if there is a threat of therapy withdrawal due to missed sessions) (M).…”
Section: Domain 1 Connecting Effectivelymentioning
confidence: 99%
“…switch to telemental health as an option when a service user is unable at short notice to attend a face-to-face appointment. CMO 2.3: Involvement and support for family and friends [89,101,[132][133][134] When family and other supporters are invited (with service user agreement) to join telemental health sessions (C), this may result in more holistic treatment planning and greater engagement of family and others in supporting service users (O1), may help improve therapeutic relationships and treatment success (O2), increase engagement (O3), reduce some uncertainty and anxiety around treatment (O4), and may increase satisfaction of and support for family and friends (O5), as family and other supporters may be able to participate in care planning meetings and assessments that they would have found it difficult to attend faceto-face, increasing their engagement in supporting service users and their understanding of their difficulties and care plans (M). This is especially helpful for 1) those living in locations different from their family and friends or where family and friends have caring or work commitments preventing them from attending meetings face-to-face 2) children and young people (as this may allow their parents to be more involved in their care); 3) service users in inpatient settings where family and friends cannot visit (for example, because of epidemicrelated restrictions) or a hospital is in a remote location.…”
Section: Domain 2 Flexibility and Personalisationmentioning
confidence: 99%